The influence of perceived social support on academic engagement among adolescents: the mediating role of self-efficacy - Tortosa Martínez, Begoña María; Pérez-Fuentes, María del Carmen; Molero Jurado, María del Mar (Anales de Psicología / Annals of Psychology, 2024)
Academic engagement is influenced by environmental and personal factors, such as perceived social support and self-efficacy. Both factors have become one of the most important elements in the academic context, due to their relationships with the school adjustment of adolescents. The objective of this study was to analyze the influence of the perceived social support of friends and family on academic engagement, as well as to check whether self-efficacy plays a mediating role in the relationship between both variables. A cross-sectional descriptive study was performed. The sample consisted of 802 secondary school students, with an average age of 13.65 years (SD = 1.24) (where 50.6% were women and 49.4% men). The results showed the existence of positive relationships between perceived social support and the dimensions of academic engagement. The mediation models showed the direct effect of perceived social support on academic engagement and the indirect effect of perceived social support on academic engagement when self-efficacy mediates in this relationship. In conclusion, it is recommended to promote self-efficacy and a positive academic path, due to the involvement of the perceived social support of friends and family in the school path and engagement to studies.